2021
DOI: 10.1088/2058-8585/ac2c50
|View full text |Cite
|
Sign up to set email alerts
|

A flexible, and wireless LED therapy patch for skin wound photomedicine with IoT-connected healthcare application

Abstract: Low-level laser therapy (LLLT), also known as photobiomodulation, is a safe and noninvasive method for various dermatological applications. However, most LLLT devices have limitations, such as low flexibility, high energy consumption, and huge equipment size, limiting their usage in daily life and clinical treatment. This study presents a flexible and wireless light emitting diode (LED) patch with an internet of thing (IoT) healthcare platform for wound healing applications. The flexible LED patch was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The use and validation of LEDs for PBM paves the way to developing wearable exposure systems for next generation wound healing in home and hospital settings 46 . The efficacy of low intensity light may be further investigated on more complex skin models, and if found capable of improving would healing outcomes, may enable the deployment of low-powered LED based wearables 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The use and validation of LEDs for PBM paves the way to developing wearable exposure systems for next generation wound healing in home and hospital settings 46 . The efficacy of low intensity light may be further investigated on more complex skin models, and if found capable of improving would healing outcomes, may enable the deployment of low-powered LED based wearables 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering photobiomodulation, a wearable PBM patch [Figure 12A] was developed, which used a flexible red-wavelength organic light-emitting diode (OLED) source, which could be attached to the human body [99] . This patch consisted of flexible OLED modules and a battery module with a patch to allow skin attachment.…”
Section: Wearable Light Stimulatorsmentioning
confidence: 99%
“…Experimental results demonstrated that this medical device accelerated the initial wound healing process through the synergetic effects of the wound dressing and LED irradiation. Reproduced with permission [99] . Copyright 2018, WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim (C) Design of wearable LED patch.…”
Section: Wearable Light Stimulatorsmentioning
confidence: 99%
See 2 more Smart Citations